Spontaneous rupture of falciparum malarial spleen presenting as hemoperitoneum, hemothorax, and hemoarthrosis - Fareed, Mohammad I. (International Scientific Literature, Inc., 2013)
Patient: Male, 29 Final Diagnosis: Spontaneous spleen rupture Symptoms: Abdominal distension • abdominal pain • abdominal tenderness • disorientation • fever • hemothorax • hip pain • reduced urine output Medication: — Clinical Procedure: Splenectomy Specialty: Infectious Diseases OBJECTIVE: Rare diseases BACKGROUND: Spontaneous rupture of a malarial spleen is uncommon even in the endemic regions of malaria. This may lead to delayed or missed diagnosis of splenic rupture, which may be life threatening. CASE REPORT: We are reporting a patient with P. falciparum malaria who developed a spontaneous splenic rupture encountered in our department. A 29-year-old male patient with history of high grade intermittent fever with chills for 4 days followed by disorientation and reduced urine output and abdominal pain with distension associated with bilateral hip pain and dyspnea with bilateral chest pain (mainly on the left side) for 1 day. There was no history of any trauma or abnormal bleeding. Investigations revealed P. falciparum malaria, hemoperitoneum, hemothorax, and hemoarthrosis. Laparotomy confirmed hemoperitoneum with about 1.5 L of blood-stained fluid, enlarged friable spleen with rupture of the splenic capsule on the inner surface, and active bleeding. Splenectomy was performed. The patient was diagnosed with malarial spleen and received antimalarial therapy. CONCLUSIONS: Splenic rupture with hemoperitoneum should be managed with laparotomy and splenectomy, along with antimalarial drugs. A high index of suspicion is needed to detect these complications early.